Study of the Structure and Electronic Properties of the ZnO Monolayer: Density Functional Theory - Raihan, Muhammad Fadlan; Wungu, Triati Dewi Kencana; Yuliarto, Brian (Computational And Experimental Research In Materials And Renewable Energy, 2021)
ZnO has received considerable attention since it has promising applications in electronic devices. Although many studies have explored the potential of ZnO as a promising material, the precise role of geometric in ZnO remains unclear. This study deals with the electronic structure of the ZnO monolayer using density functional theory (DFT). The DFT was used to investigate the band structure and density of states of the ZnO monolayer. It is observed that the structural change of ZnO from bulk to monolayer increases the bandgap by 1.84 eV without changes its natural characteristic. Moreover, This study provides information about the properties of the ZnO monolayer and its potential in electronic and magnetic devices application.